2021
DOI: 10.3389/fped.2021.672131
|View full text |Cite
|
Sign up to set email alerts
|

Fecal High-Mobility Group Box 1 as a Marker of Early Stage of Necrotizing Enterocolitis in Preterm Neonates

Abstract: Introduction: An early diagnosis of necrotizing enterocolitis (NEC), a major gastrointestinal emergency in preterm newborns, is crucial to improve diagnostic approach and prognosis. We evaluated whether fecal high-mobility group box protein 1 (HMGB1) may early identify preterms at risk of developing NEC.Materials and Methods: A case-control study including neonates admitted at the Neonatal Intensive Care Unit (NICU) of the Sapienza University Hospital “Umberto I” in Rome, from July 2015 to December 2016. Stool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 45 publications
(82 reference statements)
0
17
0
Order By: Relevance
“…HMGB1 is an important proinflammatory cytokine and inflammatory transmitter (65-67). The increased expression of HMGB1 leads to enhancement of the inflammatory response in the tissue and promotes the development of NEC (68,69). The present study showed that targeting MD2 to block the activation of TLR4 reduces excessive inflammatory storms, intestinal barrier function injury and intestinal cell apoptosis in NEC patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…HMGB1 is an important proinflammatory cytokine and inflammatory transmitter (65-67). The increased expression of HMGB1 leads to enhancement of the inflammatory response in the tissue and promotes the development of NEC (68,69). The present study showed that targeting MD2 to block the activation of TLR4 reduces excessive inflammatory storms, intestinal barrier function injury and intestinal cell apoptosis in NEC patients.…”
Section: Discussionmentioning
confidence: 99%
“…HMGB1 is an important proinflammatory cytokine and inflammatory transmitter ( 65 67 ). The increased expression of HMGB1 leads to enhancement of the inflammatory response in the tissue and promotes the development of NEC ( 68 , 69 ).…”
Section: Discussionmentioning
confidence: 99%
“…Morbidity was defined as the presence of at least one of the major prematurity-related complications, such as necrotizing enterocolitis (NEC) Bell-Stage ≥ 2, intraventricular hemorrhage (IVH), periventricular leukomalacia (PVL), sepsis proven by positive culture, retinopathy of prematurity (ROP), and bronchopulmonary dysplasia (BPD) of at least moderate grade. Diagnosis of NEC, BPD, IVH, PVL, ROP, and sepsis were performed according to standard criteria by physicians caring for the babies and were blinded of the study aims [ 22 , 23 , 24 , 25 , 26 ]. Extrauterine growth restriction (EUGR) with longitudinal definition was defined as the loss of 1 standard deviation from birth to 36 weeks of PMA [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, we collected data regarding intrauterine growth restriction (IUGR), pregnancy-induced hypertension, antenatal corticosteroids administration (as an intramuscular steroid cycle in two doses of 12 mg over a 24 h period), GA, birth weight, to be small for GA (SGA), sex, type of delivery, twin's pregnancy, pH at birth, Apgar score at 5 min after birth and respiratory distress syndrome. Data regarding nutritional intake and prematurity-related morbidities (NEC, bronchopulmonary dysplasia, sepsis proven by positive culture, retinopathy of prematurity, periventricular leukomalacia and intraventricular hemorrhage before and after 7 days of age) [27][28][29][30][31] were also collected during the entire hospital stay.…”
Section: Data Collectionmentioning
confidence: 99%